How to Strengthen Customer Loyalty with Technology - Charisma Pamungkas; Shine Pintor Siolemba Patiro; Joko Rizkie Widokarti (Jurnal Manajemen, 2025)
This research aims to investigate the antecedents of loyalty and the role of technology in the Indonesian e-commerce context based on customers' points of view. This quantitative research involves data from 317 Indonesian e-commerce customers, which is then analysed using Structural Equation Modelling with Partial Least Square method (SEM-PLS). The results show customer satisfaction, trust, and engagement significantly impact loyalty. Both Trust and Engagement act as the mediator between Satisfaction and Loyalty. Meanwhile, there are differences in how technology interacts with the equation. While it lessens the influence of Engagement on Loyalty, it will increase the influence of Trust on Loyalty. This research simultaneously adds technology into the model to test its influence on the interaction between variables. It also provides CRM research, which is conducted based on customers' points of view.